DETERMINANTS OF NON-PERFORMING LOANS AMIDST UNEXPECTED CRISES IN MALAYSIA’S COMMERCIAL BANKS - Normah Erra Zulkifli; Zuriyati Ahmad (International Journal of Accounting, Finance and Business, 2022)
Nonperforming loans ratio in Malaysian banks has been found to be continuously increasing in recent years. The emergence of unexpected crises that hit Malaysia has worsened the problems. Therefore, this paper attempts to investigate the relationship of microeconomic and macroeconomic factors amidst the unexpected crises and nonperforming loans in Malaysia. Panel data from 26 commercial banks with the period of 14 years (2007-2020) are used. Afters series of testing, Random Effect Model is utilized to analyse the model. Finding shows that microeconomic variables return on asset (ROA), loan growth (LG) and loan to asset (LTA) are highly significant in influencing the non performing loans. Nonetheless, the macroeconomic variables chosen GDP and interest rate are found not contributing to major changes on non performing loans. While unexpected crises which include Global Financial crisis and Pandemic of Covid 19 depicts significant relationship in worsening the non performing loans in commercial banks. Therefore, it is suggested that the commercial banks need to strengthen the internal bank characteristics and try to avoid major impact from the unexpected crises.